2005
DOI: 10.4067/s0717-95022005000300007
|View full text |Cite
|
Sign up to set email alerts
|

Triple Right Renal Vein: An Uncommon Variation

Abstract: SUMMARY:We report an unilateral three renal veins the right kidney in an elderly male cadaver. They were three calibrous veins having independent courses up to the inferior vena cava. No other vascular anomalies were noted in this specimen. This anatomical curiosity should be kept in mind by clinicians and academics that may manipulate this anatomical area. KEY WORDS:Anatomy; Anomalies; Human; Kidney; Vein. Case ReportDepartment of Morphology, Biomedical Institute, Fluminense Federal University, RJ, Brazil. 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…An error of fusion of these two vessels, thus causing their persistence, may result in bilateral or unilateral duplication of these vessels [10]. Occurrences of multiple renal veins are relatively common, and several authors have reported large numbers of venous variations resulting from embryonic developmental errors [1], [5], [11][12][13]. According to Kaneko, Kobayashi and Okada [14], the renal veins present fewer variations than do the renal arteries, and multiple renal veins are more common on the right side than on the left-sid [8].…”
Section: Discussionmentioning
confidence: 99%
“…An error of fusion of these two vessels, thus causing their persistence, may result in bilateral or unilateral duplication of these vessels [10]. Occurrences of multiple renal veins are relatively common, and several authors have reported large numbers of venous variations resulting from embryonic developmental errors [1], [5], [11][12][13]. According to Kaneko, Kobayashi and Okada [14], the renal veins present fewer variations than do the renal arteries, and multiple renal veins are more common on the right side than on the left-sid [8].…”
Section: Discussionmentioning
confidence: 99%
“…A rare case of three renal veins draining the right kidney and separately joining the inferior vena cava with inferior renal vein receiving right testicular vein was reported earlier [19].…”
Section: Discussionmentioning
confidence: 99%
“…Fernandes et al [7] suggested the embryological basis for the development of additional right renal vein that there was an error on the fusion of the branches to the dorsal mesonephros derived from the right postcardinal vein, the dorsal -medial branches of the right supracardinal vein and the ventral branches of the right subcardinal vein (the latter represented by the IARV, marked by the presence of its testicular tributary). Bergman et al [3] observed that, the renal veins show less variation than do the renal arteries and multiple renal veins to be rare on the left side (1%) and common on the right side (28%).…”
Section: Discussionmentioning
confidence: 99%